Neuroimaging markers of dual impairment in cognition and physical performance following stroke: The Nor-COAST study - Einstad, Marte Stine; Schellhorn, Till; Thingstad, Pernille; Lydersen, Stian; Aamodt, Eva Birgitte; Beyer, Mona Kristiansen; Saltvedt, Ingvild; Askim, Torunn (Frontiers in Aging Neuroscience, 2022)
Background Cognitive decline and decline in physical performance are common after stroke. Concurrent impairments in the two domains are reported to give increased risk of dementia and functional decline. The concept of dual impairment of physical performance and cognition after stroke is poorly investigated. Clinically accessible imaging markers of stroke and pre-existing brain pathology might help identify patients at risk. Objective The primary aim of this study was to investigate to which extent pre-stroke cerebral pathology was associated with dual impairment in cognition and physical performance at time of stroke. Secondary aims were to examine whether white matter hyperintensities, medial temporal lobe atrophy, and stroke lesion volume and location were associated with dual impairment. Methods Participants from the Norwegian Cognitive Impairment After Stroke (Nor-COAST) study with available MRI data at baseline were included in this cross-sectional study. Logistic regression analyses were conducted, with impairment status (no impairment, impaired cognition, impaired physical performance, and dual impairment) as the dependent variable and MRI markers as covariates. Pre-existing brain pathologies were classified into neurodegenerative, cerebrovascular, or mixed pathology. In addition, white matter hyperintensities and medial temporal lobe atrophy were included as independent covariates. Stroke volume and location were also ascertained from study-specific MRI scans. Results Participants’ (n = 348) mean (SD) age was 72.3 (11.3) years; 148 (42.5%) were women. Participants with dual impairment (n = 99) were significantly older, had experienced a more severe stroke, and had a higher comorbidity burden and poorer pre-stroke function. Stroke lesion volume (odds ratio 1.03, 95%, confidence interval 1.00 to 1.05, p = 0.035), but not stroke location or pre-existing brain pathology, was associated with dual impairment, after adjusting for age and sex. Conclusion In this large cohort of stroke survivors having suffered mainly mild to moderate stroke, stroke lesion volume—but not pre-existing brain pathology—was associated with dual impairment early after stroke, confirming the role of stroke severity in functional decline.